Analisis Korelasi Kelembaban Udara terhadap Epidemi Demam Berdarah yang Terjadi di Kota Bengkulu - Masjuwita, Masjuwita; Endang Sartati; Abdullah Ibrahim; Reflis, Reflis; Satria Putra Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Dengue (Dengue Fever) is a vector bone disease caused by the Aedes Aegepty Mosquito. The aim of this research is to determine the relationship between air humidity levels and the Dengue Fever epidemic that occurred in Bengkulu Municipality. This research is a type of descriptive research with quantitative methods which aims to determine and show the relationship between air humidity levels and cases of Dengue Fever (DHF). This research was conducted in the Municipality of Bengkulu, using quantitative data on air humidity obtained from the Climatology Station (Meteorology, Climatology and Geophysics Agency) Baai Island, Bengkulu City, namely air humidity data from 2009 to 2014 and data on Dengue Fever cases in the Municipality obtained from the Department Bengkulu Province Health from 2009 to 2014 data. Judging from the results, the level of increase in air humidity in Bengkulu Municipality in 2009-2014 ranged from 82% - 86%. It can be seen that the number of dengue fever cases in Bengkulu Municipality in 2009-2014 was around 173 - 472 people. Data processing was carried out by computer using SPSS and Microsoft Excel programs. The results of the analysis using the bivariate test show that air humidity has a relationship between the incidence of Dengue Fever that occurs in the Municipality of Bengkulu, with a value of r=0.408 and p-value=0.007.